Major adverse cardiovascular events associated with testosterone treatment: a pharmacovigilance study of the FAERS database - Zhao, Hui; Li, Jun-Min; Li, Zi-Ran; Zhang, Qian; Zhong, Ming-Kang; Yan, Ming-Ming; Qiu, Xiao-Yan (Frontiers in Pharmacology, 2023)
Abstract Background Testosterone is an essential sex hormone in maintaining masculine characteristics which is prescribed for male hypogonadism as testosterone replacement treatment (TRT). Herein, we investigated longstanding controversial about the association between TRT and major adverse cardiovascular events (MACE), based on real world adverse event (AE) reports, registered in the Food and Drug Administration Adverse Event Reporting System (FAERS). Methods Publicly available FAERS data from January 1 2004 to December 31 2022 were retrieved from FDA website. Data mining protocol including reporting odds ratio (ROR) and Bayesian confidence propagation neural network (BCPNN) were applied to analyze overreporting caused by risk factors and MACE, including TRT, morbidities and age. ROR and BPCNN were also applied to investigate the annually developing trend of pharmacovigilance (PV) signals in real world retrospectively. Results A total of 3,057 cases referring to MACE, with a median age of 57 years old (yo), were identified from 28,921 cases of testosterone user. MACE related PV signals emerged since 2014, including cardiac death, non-fatal myocardial infarction, non-fatal stroke. Myocardial infarction (MI) (ROR 9.46 IC025 3.08), acute myocardial infarction (AMI) (ROR 16.20 IC025 3.72), ischemic cardiomyopathy (ROR 11.63 IC025 2.20) and cardiomyopathy (ROR 5.98 IC025 1.96) were the most significant signals generated, as well as weaker signals including cardiac failure acute (ROR 4.01 IC025 0.71), cardiac arrest (ROR 1.88 IC025 0.56) and ventricular fibrillation (VF) (ROR 2.38 IC025 0.38). Time to onset (TTO) of MACE was calculated with a median 246 days for AMI. Conclusion For myocardial infarction and cardiomyopathy, TRT tended to increase the risk of MACE, statistically; while for cardiac arrhythmia, cardiac failure and stroke, TRT demonstrated beneficial effects among population with morbidities such as testosterone deficient (TD), diabetes mellitus (DM) and hypertension. MACEs were rare but leading to serious outcomes including significant increase in death and disability. Since 2018, as well as before 2014, reports referring to TRT associated with MACE was relatively scarce, which indicated that there might be considerable cases went unrecorded, due to neglection. Health workers and testosterone users might pay more attention to testosterone-induced MACE.